Die Kunst der Taktik - Arrianus, Flavius (Sammlung Tusculum, 2017)
"The art of tactics has already fascinated the ancient world. What tactics did Alexander the Great use for the conquest of his huge empire? What can the Romans learn about it? And how do you train an army today? Answers to such questions and a unique insight into ancient tactics are provided by Arrianus (2nd century AD) in his Techne Taktike and Asclepiodotus in a work of the same title, which also employs diagrams to illustrate the text."--Provided by publisher